The factors that affect employees performance at TNB Kulaijaya / Rafiqah Ramli - Ramli, Rafiqah (2014)
The objective of this study was to investigate performance appraisal and motivation towards employee performance in TNB Kulaijaya. Employees who are work at TNB Kulaijaya were used as respondents for this study. A field survey was conducted also at TNB Kulaijaya at each department to identify the positive relationship between employee’s performance and performance appraisal, and to identify positive relationship between employee’s performance and motivation in TNB Kulaijaya. A total of 110 questionnaires were distributed to the respondents and were usable for data analysis. Demographic background was analysed using Frequency Analysis. Descriptive Analysis was applied on the main variables of the study. Using Reliability Analysis, all items in the survey were found to be reliable. Pearson Correlation Analysis shows that all dependent variables (performance appraisal, motivation) were positively correlated with the dependent variable (employee’s performance). Multiple Regression Analysis result showed that motivation value was the strongest variable for employee’s performance in this study, followed by performance appraisal.